Performance improvement of distributed combined cycle plants through modification of structure. (September 2017) - Kalina, Jacek
Abstract: In this paper possible modifications of combined cycle power plants of electric power output below 50 MW are presented. The concept is based on modified configuration of a single pressure heat recovery steam generator and bigger number of system components. Alternative plant structures are examined theoretically using fundamental thermodynamic relations. Simulations were performed using the Engineering Equation Solver software package. Results show that there is a room for both efficiency and flexibility improvements. In the simulated cases the energy conversion efficiency of a combined cycle power plant increased from 49.9% up to 52.7%. In addition to this, design parameters such as gas turbine pressure ratio, combustion temperature, steam pressure are relatively low, in the range of values currently widely used in industry. The concept also assumes a bigger role of the ORC technology. Its share in the total power output increased from 5.5% in the reference case up to 12.6% in the configuration that achieves the highest value of energy efficiency.